Ownership Concentration and Firm Value : A Panel Data Analysis on The Impact of Ownership Concentration on Firm Value - Atmaja, Lukas Setia (Universitas Prasetiya Mulya, 2009)
This study examines the impact of ownership concentration on firm value. This study finds a negative and significant relationship between ownership concentration (measured by aggregate substantial shareholdings and the presence of controlling shareholders) and firm value. This suggests that large or controlling shareholders can extract the private benefits of control which in turn leads to lower firm value. The results support the rent extraction hypothesis, but not the agency relationship.